2014
DOI: 10.1159/000362371
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Is Produced by Retinal Glial Cells and Inhibits the Growth of Vascular Endothelial Cells

Abstract: Background/Aims: By the release of antiangiogenic factors, Müller glial cells provide an angiostatic environment in the normal and ischemic retina. We determined whether Müller cells produce thrombospondin-1 (TSP-1), a known inhibitor of angiogenesis. Methods: Secretion of TSP-1 by cultured Müller cells was determined with ELISA. Slices of rat retinas and surgically excised retinal membranes of human subjects were immunostained against TSP-1 and the glial marker vimentin. The effects of TSP-1 on the growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…NR4A2, acting as a transcription factor, induced cell differentiation and maintained dopaminergic neurons 24 , 25 . THBS1 is an adhesive glycoprotein and affects cell adhesion and cell migration 26 , 27 . Activated Notch signaling attenuates HPV-induced cervical cell transformation while its inactivation promotes cell transformation and carcinogenesis 2 , 7 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…NR4A2, acting as a transcription factor, induced cell differentiation and maintained dopaminergic neurons 24 , 25 . THBS1 is an adhesive glycoprotein and affects cell adhesion and cell migration 26 , 27 . Activated Notch signaling attenuates HPV-induced cervical cell transformation while its inactivation promotes cell transformation and carcinogenesis 2 , 7 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…MGCs and ECs cooperate in remodelling of the extracellular matrix by secreting MMPs and in retinal angiogenesis by the secretion of trophic factors (Jacobo & Kazlauskas, ; Lorenc, Jaldin‐Fincati, Luna, Chiabrando, & Sanchez, ). In addition, once the angiogenesis process has ended, MGCs secrete thrombospondin‐1 to arrest endothelial proliferation (Yafai et al., ).…”
Section: Mgcs In Healthmentioning
confidence: 99%
“…Adenosine binds to G-protein-linked receptors which can be classified into the A 1 , A 2A , A 2B , and A 3 , 4 subtypes. It has been confirmed that all the four types of adenosine receptors exist in the retina [7][8][9]. Previous studies have demonstrated that A 2A receptor (A 2A R) promotes the release of glutamate and that A 2A R antagonists decrease its release.…”
Section: Introductionmentioning
confidence: 77%